OPERATIONAL STATUS OF IRON FOLIC ACID TABLETS SUPPLEMENTATION TO ADOLESCENT GIRLS – A CROSS SECTIONAL STUDY IN A RURAL DISTRICT OF INDIA - SUMITRA PATTANAIK,; LIPILEKHA PATNAIK,; TRILOCHAN SAHU,; E VENKATA RAO, (International Journal of Pharma and Bio Sciences, 2015)
In India, prevalence of anemia in adolescent girls is around 56%, ranging from 33% in Andhra Pradesh to 98% in Rajasthan. This study was undertaken to assess the operational status of weekly iron and folic acid supplementation programme. It was a community based cross-sectional study in the rural villages of Khordha district of Odisha. 30 villages were selected by cluster sampling technique and 10 girls of 10-19 years age from each village/cluster were included in the study. A total of 299 adolescent girls were interviewed, anthropometric measurements were done and haemoglobin was estimated by Sahli’s method. The prevalence of anemia was found to be 83.95% and associated with mother’s education, socio-economic status of the family, excessive menstrual bleeding, iron intake, nutritional status and worm infestation. 73% of adolescent girls had taken IFA (iron & folic acid) tablet at some time. There is a need for periodic screening of adolescents along with counselling of adolescents and capacity building of the stake holders.